(untitled) (Research, Society and Development, 2022)
Introduction: The mandibular third molars are the teeth that are most frequently included or semi-included. Exodontia of these elements is a common procedure performed in oral and maxillofacial surgery clinics and hospitals. The prophylactic removal or maintenance in the arch of mandibular third molars generates controversy among authors and surgeons, and should be performed by analyzing each case individually. Objective: This study aims to compare the results of the use of exodontia and coronectomy techniques in the surgical approach of mandibular third molars intimal to the mandibular canal. Methodology: A narrative literature review was conducted using papers from 2004 to 2022 found in Scielo and PubMed data platforms. Discussion: Intentional partial odontectomy (IPO) is considered a safe and effective technique capable of limiting the incidence of damage to the NAI. Most of the studies analyzed reported a lower incidence of inferior alveolar nerve injury when the coronectomy technique was used compared to conventional exodontia and no study found permanent injury to this nerve. Conclusion: In this context, based on the information collected in the literature, one can see that coronectomy, when correctly indicated and performed, is considered by many authors a safe technique to be used in clinical practice.